Gender, criminalization, imprisonment and human rights in southeast Asia - Jefferson, Andrew M.; Jeffries, Samantha (Emerald studies in activist criminology, 2022)
This volume contains two Open Access Chapters. Gender, Criminalization, Imprisonment and Human Rights in Southeast Asia features contributions from activist scholars grappling to understand and alleviate the compound sufferings of women and LGBTIQA+ persons as they encounter Southeast Asian criminal justice systems. The collection demonstrates that it is critical that the drivers of gendered harms and the way gendered needs intersect with other inequalities are better understood and adequately reflected in law, policy and practice.